Discovering computers complete : your interactive guide to the digital world - Shelly, Gary B.; Vermaat, Misty (Boston, Massachusetts : Course Technology, Cengage Learning, 2012)
Students are guided through the latest trends in computer concepts and technology in an exciting and easy-to-follow format. Updated for currency, discovering computers: complete provides the most up-to-date information on the latest technology in today's digital world
1. Introduction to computers -- 2. Internet and world wide web -- 3. Application software -- 4. Components of the system unit -- 5. Input -- 6. Output -- 7. Storage -- 8. Operating systems and utility programs -- 9. Communications and networks -- 10. Database management -- 11. Computer security and safety, ethics, and privacy -- 12. Information system development -- 13. Programming languages and program development -- 14. Enterprise computing -- 15. Computer careers and certification
Includes index
Keywords: Computer science; Computers